Handlungsoptionen auf dem Weg in die Gigabit-Gesellschaft Eine rechtliche Analyse von Konzessions- und Kooperationsmodellen sowie regulatorischer Entflechtungsbestimmungen - Toros, Fabian (Nomos Verlagsgesellschaft mbH & Co. KG, 2021)
As a matter of fact, the expansion of very high capacity networks is a central challenge of the present. However, political goals and the reality of expansion are far apart. In answer to the question of feasibility, this thesis examines various approaches to accelerate the expansion of optical fibre networks within the field's complex legal framework. In these premises, the following issues need to be clearified: Is an economically and technically sensible approach permissible under the law? If yes, are there any legal barriers or other reasons for problems in implementation? Considering the circumstances, are these options for action ultimately viable?